Everyday Econometricians: Selection Neglect and Overoptimism When Learning from Others - Barron, Kai; Huck, Steffen; Jehiel, Philippe (American Economic Journal: Microeconomics, 2024)
This study explores selection neglect in an experimental investment game where individuals can learn from others' outcomes. Experiment 1 examines aggregate-level equilibrium behavior. We find strong evidence of selection neglect and corroborate several comparative static predictions of Jehiel's (2018) model, showing that the severity of the bias is aggravated by the sophistication of other individuals and moderated when information is more correlated across individuals. Experiment 2 focuses on individual decision-making, isolating the influence of beliefs from possible confounding factors. This allows us to classify individuals according to their degree of naivety and explore the limits of, and potential remedies for, selection neglect.
Keywords: Micro-Based Behavioral Economics; Behavioral Finance; Consumer Economics; Econometricians